Associação entre risco cardiovascular e controle autonômico cardíaco em portadores de HIV - Kuinchtner, Gabriela Castro (2015)
Introduction: The increase of cardiovascular disease risk has been demonstrated in subjects with HIV infection. The dysfunction in the regulation of the autonomic system has been identified as a mechanism underlying to cardiac death in this group of patients. This study aimed to analyze the association between cardiovascular risk and cardiac autonomic control in patients with HIV. Methods: The sample consisted of 25 patients with HIV, of both genders, in use of antiretroviral therapy and with undetectable viral load, treated on the of Infectious Diseases Ambulatory, from the University Hospital of Santa Maria (HUSM), between August and December of 2014. Patients with cardiovascular disease, metabolic, respiratory, neurological or kidney were excluded. The cardiovascular risk was assessed by Framingham score, used to estimate the probability of cardiovascular events in ten years. The cardiac autonomic control was assessed by measuring the heart rate variability, analyzing the following variables: 1) in the time domain were measured SDNN, triangular index (overall variability) and rMSSD (parasympathetic activity); 2) in the frequency domain understood the low frequency components (LF; sympathetic activity) and high frequency (HF; parasympathetic activity), both normalized, and the LF/HF ratio (sympatho-vagal balance). Results: The sample (12 women and 13 men) had a mean age of 48.7±10.9 years, body mass index of 25.7±5.1 kg/m2, heart rate of 72.1±13.4 bpm, respiratory rate of 16.3±3.8 bpm, systolic blood pressure of 125.2±18.7 mmHg and diastolic 83.3±12.2 mmHg. The average time since diagnosis of the disease was 10.2±5.0 years, the medication time of 7.2±4.2 years and the CD4 count of 628.6±223.8 mm3 of blood. The score obtained in the Framingham score was 9.5±5.1 and the risk of cardiovascular events was 9.5±7.9%, with 7 patients classified as low risk, 14 as intermediate risk and 4 as high cardiovascular risk. The Framingham score presented a correlation with the medication time (r=0.53), with the LFnu component (r=0.45) and with the ratio LF/HF (r=0.44), but it was inversely correlated with SDNN (r=-0.43), rMSSD (r=-0.47) and with the triangular index (r=-0.49). The risk of cardiovascular events was positively correlated with the medication time (r=0.54), with the LFnu component (r=0.45) and with the ratio LF/HF (r=0.45), but had negative correlation with SDNN (r=-0.40), rMSSD (r=-0.43) and the triangular index (r=-0.48). Conclusion: Patients with HIV classified into different bands of Framingham score, presented association between cardiovascular risk and increased sympathetic activity, decreased parasympathetic activity and sympatho-vagal balance. This demonstrates that even in patients with undetectable viral load, cardiovascular autonomic dysfunctions may be associated with cardiovascular risk in ten years. These findings point to the importance of routine assessments of cardiovascular autonomic nervous system in this population.